2013
DOI: 10.1016/j.ijhydene.2013.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Study of the cycle-to-cycle variations of an internal combustion engine fuelled with natural gas/hydrogen blends from the diagnosis of combustion pressure

Abstract: Spark ignition engine Combustion diagnosisAlternative fuels Genetic algorithm a b s t r a c tA methodology is presented for studying the influence of using alternative fuels on the cycle-to-cycle variations of a spark ignition engine which has been fuelled with mixtures of natural gas and hydrogen in different proportions (0e100%). The experimental facility consists of a single-cylindrical spark ignition engine coupled to an asynchronous machine IntroductionBecause of the increasing concern about energy defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…It is observed in Figure 5(a) and 5(b) that COVs for Pmax are relatively small (<%) for both test fuels and COV for frequency distributions of 5% MFB, 10% MFB, 50% MFB and 90% MFB are also small for conventional diesel and palm biodiesel. These results are parallel with previous studies on engine cycle-to-cycle variation related to biodiesel fuel properties [35,36]. A drawback of the conventional diesel engine is when the COV IMEP exceeds 10%, drivability problems in vehicles could arise.…”
Section: Resultssupporting
confidence: 88%
“…It is observed in Figure 5(a) and 5(b) that COVs for Pmax are relatively small (<%) for both test fuels and COV for frequency distributions of 5% MFB, 10% MFB, 50% MFB and 90% MFB are also small for conventional diesel and palm biodiesel. These results are parallel with previous studies on engine cycle-to-cycle variation related to biodiesel fuel properties [35,36]. A drawback of the conventional diesel engine is when the COV IMEP exceeds 10%, drivability problems in vehicles could arise.…”
Section: Resultssupporting
confidence: 88%
“…The parameters k wos1 and k wos2 are multipliers that have to be adjusted. More details of the thermodynamic model can be found in Reyes et al [24].…”
Section: Models Employed 221 Thermodynamic Modelmentioning
confidence: 99%
“…The general objective of the optimization procedure is to reduce the error of the fitness function, both for motored (mass fraction burned zero) and combustion (mass fraction burned unity) conditions. Detailed information of the crossover function and the Z function can be found in Reyes et al [24] where a full description of the genetic algorithm is presented with supplementary information.…”
Section: Genetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that hydrogen addition contributes to reducing the duration of flame development, which has highly positive effects on reducing cycle-by-cycle variations. Reyes et al [23] characterized mixtures of natural gas and hydrogen in a single-cylinder spark ignition engine by means of a zero dimensional thermodynamic model.…”
Section: Introductionmentioning
confidence: 99%